Dark Skies (Taylor & Francis, 2023)
Dark Skies addresses a significant gap in knowledge in relation to perspectives from the arts, humanities, and social sciences. In providing a new multi- and interdisciplinary field of inquiry, this book brings together engagements with dark skies from a variety of disciplinary backgrounds, empirical studies, and theoretical orientations.